CAESAR, DE BELLO CIVILE 3, 88, 3 - Amela Valverde, Luis (Myrtia, 2003)
In De Bello Civile 3, 88, 3, Caesar, when enumerating the pompeians troops that will combat him in Pharsalus , mentions some cohortes Hispaniae that had been brought by Afranius. In this paper, the origin of these units is studied, without a doubt belonging to the army of the Hither Spain, as well as its relationship the pompeian clientship.